Collaborative Governance in Tuberculosis Eradication: A Case Study of Yamali Civil Society Organization in South Sulawesi, Indonesia - Amir, Muhammad Yusran; Nurhayani, Nurhayani (Media Publikasi Cendekia Indonesia, 2025)
Tuberculosis (TB) is an infectious disease that still poses a major challenge for public health globally, including in Indonesia. Based on the Global Tuberculosis Report 2024, the number of TB cases continues to increase every year. One of the initiatives that supports TB eradication in South Sulawesi is the active role of the Tuberculosis Care Community Foundation (Yamali), which collaborates with the government, health facilities, and the community to reduce the prevalence of TB. This study aims to analyze the dynamics of collaboration and collaborative actions by the Yamali NGO in efforts to eradicate TB in South Sulawesi. The method used in this study is a qualitative approach with data collection through in-depth interviews and document reviews. Eight research informants were selected by purposive sampling based on their involvement in the TB eradication program. The results of this study show that the collaboration between the Makassar City Health Office, the Ministry of Health, the Regional Government, and Yamali has been effective. Treatment assistance programs, community empowerment, and new case discovery were found to have been implemented well. However, challenges related to case recording in the TB Information System Software (SITB) must be improved to cover all cases, including those carried out independently by patients. The sustainability of this collaboration is the main key to achieving the TB elimination target in Makassar City. We recommend making a policy for pentahelix collaboration i.e. government, business, civil society, academician and media